Barriers to academic success: An impact analysis of international students in China - Haijun, Dong; Zubair, Asim; Fatima, Sonia (Journal of International Students, 2026)
This study examined factors influencing academic success among international students at Hohai University using survey data from 262 students. Analysis via SPSS 26 and PLS-SEM revealed strong measurement model reliability (composite reliability: 0.84–0.91; factor loadings: 0.72–0.88; AVE > 0.50). Hierarchical regression explained 74% of graduation success variance (R² = 0.74). Significant positive predictors included commitment to graduate (β = 0.35, p < 0.001), time management (β = 0.28, p < 0.001), language proficiency (β = 0.26, p < 0.001), and cultural adaptation (β = 0.20, p = 0.002). Study suspension history (β = −0.24, p < 0.001) and emotional difficulties negatively impacted outcomes. PLS-SEM confirmed academic barriers (β = −0.42, p < 0.001) and social barriers (β = −0.31, p < 0.001) reduced success, while institutional support facilitated it (β = 0.38, p < 0.001). Findings underscore needs for language support, cultural integration, and targeted interventions.